2006
DOI: 10.1111/j.1365-2929.2006.02389.x
|View full text |Cite
|
Sign up to set email alerts
|

Training the clinical eye and mind: using the arts to develop medical students' observational and pattern recognition skills

Abstract: Introduction  Observation, including identification of key pieces of data, pattern recognition, and interpretation of significance and meaning, is a key element in medical decision making. Clinical observation is taught primarily through preceptor modelling during the all‐important clinical years. No single method exists for communicating these skills, and medical educators have periodically experimented with using arts‐based training to hone observational acuity. The purpose of this qualitative study was to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(177 citation statements)
references
References 11 publications
7
167
1
2
Order By: Relevance
“…When examining art that contained less familiar imagery and representations, such as surrealist and abstract pieces, medical students still experienced improvements in skills that would help them in clinical settings [6]. After undergoing a curriculum of three two-hour sessions that included abstract art, students reported that they were able to develop a systematic approach to the visual world and found that they were able to identify patterns more readily, a skill which would translate into improved ability to make connections between patient cases [6]. In addition to developing pattern recognition skills, studying non-representational art encourages creative, on-the-spot interpretation because of its dearth of familiar imagery.…”
Section: H U M a N I T I E Smentioning
confidence: 99%
“…When examining art that contained less familiar imagery and representations, such as surrealist and abstract pieces, medical students still experienced improvements in skills that would help them in clinical settings [6]. After undergoing a curriculum of three two-hour sessions that included abstract art, students reported that they were able to develop a systematic approach to the visual world and found that they were able to identify patterns more readily, a skill which would translate into improved ability to make connections between patient cases [6]. In addition to developing pattern recognition skills, studying non-representational art encourages creative, on-the-spot interpretation because of its dearth of familiar imagery.…”
Section: H U M a N I T I E Smentioning
confidence: 99%
“…Newer approaches in clinical anatomy teaching involve using multi-media programs to digitally explore anatomical features ('An@tomedia', 2002) as well as life drawing and body painting anatomical features on living models (McMenamin, 2008). The value of incorporating art when learning clinical skills in medical education has been investigated in a number of studies (Elder, Tobias, Lucero-Criswell, & Goldenhar, 2006;Kirklin, Duncan, McBride, Hunt, & Griffin, 2007;McMenamin, 2008;Moore, Lowe, Lawrence, & Borchers, 2011;Naghshineh et al, 2008;Naug, Colson, & Donner, 2011;Schaff, Isken, & Tager, 2011;Shapiro, Rucker, & Beck, 2006). One study has examined the potential learning benefits for medical students involved in an interdisciplinary drawing module (Lyon, Letschka, Ainsworth, & Haq, 2013).…”
Section: Integration Of Art In Medical Educationmentioning
confidence: 99%
“…23 It is not surprising that a recent systematic review concluded that computerized clinical decision support systems improve clinician performance. 24 Previous studies [25][26][27] suggest that the use of a validated clinical risk score may improve clinician's performance and assist in providing more accurate prognostic information when counseling patients with stroke and their families. For example, The Clinician Judgment Versus Risk Score to Predict Stroke Outcomes (JURaSSiC) study assigned 111 clinicians with expertise in acute stroke care to predict the probability of outcomes of 5 ischemic stroke case scenarios.…”
Section: Do Clinicians Really Need Risk Scores To Make More Accurate mentioning
confidence: 99%
“…These shortcuts are usually based on pattern recognition (eg, patients with low or high probability of achieving a good outcome), whereas intermediary cases need systematic generation and testing of hypotheses. 1,27,30,32,33 Cultural Organization: Social Influence in Decisions Making…”
Section: Strokementioning
confidence: 99%